Does outsourcing affect agricultural productivity of farmer households? Evidence from China. Issue 4 (13th August 2020) - Deng, Xin; Xu, Dingde; Zeng, Miao; Qi, Yanbin
Abstract : Purpose: Previous studies focused on the influence of outsourcing (labor division) on productivity, especially in the industrial economy. However, few studies have focused on how labor division in agriculture affects agricultural productivity. To bridge this gap, this study uses survey data from 4864 farmer households in China to explore the impacts of outsourcing on agricultural productivity. Design/methodology/approach: This study employs an endogenous switching regression to account for selection bias and a counterfactual framework to measure the degree of influence. Thus, this study analyzes determinants of outsourcing and the impacts of outsourcing on agricultural productivity under the same framework. Findings: The results revealed the following. (1) Farmer households with the below average productivity tended to outsource; conversely, farmer households with the above average productivity tended to cultivate the land by themselves. (2) Productivity increased by 25.61% for farmer households who choose to outsource. Moreover, if nonoutsourcing farmer households would choose to outsource, their productivity would increase by 10.86%. Originality/value: This study furthers one's understanding of how outsourcing affects agricultural productivity among farmer households.